2016
DOI: 10.4401/ag-6863
|View full text |Cite
|
Sign up to set email alerts
|

Criticality features in ultra-low frequency magnetic fields prior to the 2013 M6.3 Kobe earthquake

Abstract: <p>The nonlinear criticality of ultra-low frequency (ULF) magnetic variations is investigated before a particular earthquake (EQ) occurred in Kobe on April 12, 2013, by applying the “natural time” analysis on a few ULF parameters: <em>F</em><span><em><sub>h</sub></em></span>, <em>F</em><span><em><sub>z</sub></em></span> and <em>D</em><span><em><sub>h</sub></em></spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Natural time was introduced [ 5 ] in 2001 as a general method to analyze time-series resulting from complex systems [ 7 ]. It has been applied to a variety of fields, such as condensed matter physics [ 22 , 23 , 24 ], geophysics [ 6 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], civil engineering [ 35 , 36 , 37 , 38 ], climatology [ 39 , 40 , 41 , 42 ], and biomedical engineering [ 43 , 44 ]. Within the concept of NTA, it has been shown that the variance of natural time may be considered as an order parameter for seismicity [ 3 , 45 , 46 , 47 , 48 , 49 ] as well as in acoustic emission before fracture [ 28 , 50 ] or in other self-organized critical phenomena such as ricepiles [ 51 ] and avalanches in the Olami–Feder–Christensen [ 52 ] earthquake model [ 53 ] or in the Burridge–Knopoff [ 54 ] train model [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural time was introduced [ 5 ] in 2001 as a general method to analyze time-series resulting from complex systems [ 7 ]. It has been applied to a variety of fields, such as condensed matter physics [ 22 , 23 , 24 ], geophysics [ 6 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], civil engineering [ 35 , 36 , 37 , 38 ], climatology [ 39 , 40 , 41 , 42 ], and biomedical engineering [ 43 , 44 ]. Within the concept of NTA, it has been shown that the variance of natural time may be considered as an order parameter for seismicity [ 3 , 45 , 46 , 47 , 48 , 49 ] as well as in acoustic emission before fracture [ 28 , 50 ] or in other self-organized critical phenomena such as ricepiles [ 51 ] and avalanches in the Olami–Feder–Christensen [ 52 ] earthquake model [ 53 ] or in the Burridge–Knopoff [ 54 ] train model [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the successful application of the NT analysis to cases of EM phenomena appearing prior to significant EQs [Potirakis et al, 2013[Potirakis et al, , 2016Hayakawa et al, 2015aHayakawa et al, , 2015b, in this work we focus on the NT analysis of air ion density variations, because they were recorded at a ground-based ion observatory of Sendai, in Japan. Several time periods for which the air ion density variations present critical behavior are revealed, which seem to precede the occurrence of significant EQs.…”
Section: _____________________________________________________________________________________mentioning
confidence: 99%
“…Since this is the first attempt to analyze the ion density in the air using the NT method, the first step is to define the way of application of NT analysis and specifically the way that the notion of the "energy" k Q of the th k event, which is used in NT analysis (see Section 3), is defined. It has to be mentioned that air ion density is of non-dichotomous nature, while its sampling is quite fast (1 sample per 20 sec), as for example compared to the ULF characteristics corresponding to the magnetic field variation recorded prior to significant EQs (1 sample per day) which have also been analyzed using the NT method [Hayakawa et al, 2015a[Hayakawa et al, , 2015bPotirakis et al, 2016]. Therefore, on one hand there is a need to use an appropriately selected threshold to define k Q , while on the other hand it is practically impossible (mainly due to computer memory restrictions, but also in terms of processing time) to process the time series if each air ion density value above the threshold is considered an individual k Q .…”
Section: Analysis Of the Air Ion Density Datamentioning
confidence: 99%
“…The applications of NTA that have appeared up to 2010 have been reviewed in the monograph by Varotsos et al [4], providing examples in various disciplines such as Statistical Physics, Condended Matter Physics, Geophysics, Seismology, Biology, and Cardiology. Since 2011, various newer applications have appeared in a variety of scientific fields, such as condensed matter and materials [17][18][19], geosciences [20][21][22][23][24][25][26][27][28], engineering [29][30][31][32][33][34][35][36], climate change [37][38][39][40], and cosmic rays [41]. Earthquake nowcasting introduced by Rundle et al [42], which is the most recent method for seismic risk estimation by means of the earthquake potential score (EPS), is also based on the concept of natural time.…”
Section: Introductionmentioning
confidence: 99%